2010
DOI: 10.14411/eje.2010.004
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild interactions between the predatory hoverfly Episyrphus balteatus (Diptera: Syrphidae) and the Asian ladybird, Harmonia axyridis (Coleoptera: Coccinellidae): Effect of larval tracks

Abstract: Abstract. The effects of the larval tracks of Episyrphus balteatus DeGeer (Diptera: Syrphidae) and Harmonia axyridis Pallas (Coleoptera: Coccinellidae) on the egg laying behavior of females of the predatory hoverfly E. balteatus were investigated in two-choice experiments. The oviposition response of H. axyridis to larval tracks of E. balteatus was also tested in one-choice experiments. Gravid E. balteatus females laid significantly fewer eggs on leaf discs with aphids and contaminated with tracks of conspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Finally, IGP experiments involving immature stages do not consider potential avoidance behaviors of adult females when selecting oviposition sites. Putra et al (2009) and Almohamad et al (2010) demonstrated that E. balteatus females laid significantly fewer eggs on leafs contaminated with larval tracks of H. axyridis, thus reducing the risk of predation to their progeny. An appropriate selection of oviposition sites by E. balteatus is crucial given the limited mobility of its larvae, preventing migration when prey become scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IGP experiments involving immature stages do not consider potential avoidance behaviors of adult females when selecting oviposition sites. Putra et al (2009) and Almohamad et al (2010) demonstrated that E. balteatus females laid significantly fewer eggs on leafs contaminated with larval tracks of H. axyridis, thus reducing the risk of predation to their progeny. An appropriate selection of oviposition sites by E. balteatus is crucial given the limited mobility of its larvae, preventing migration when prey become scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Episyrphus balteatus pupae were never attacked by C. septempunctata adults or larvae (Hindayana et al 2001 ). axyridis larval tracks (Almohamad et al 2010 ). axyridis larval tracks (Almohamad et al 2010 ).…”
Section: Intraguild Predation On Intraguild Parasitoidsmentioning
confidence: 99%
“…The distribution of oviposition sites among conspecific females is of prime importance because it allows them to share resources by partitioning their niches (Sicsú et al, 2015). A few laboratory and semi-field studies suggest that H. axyridis is deterred from ovipositing in the presence of conspecifics, whereas heterospecific competitors do not influence oviposition site selection (Yasuda et al, 2000;Almohamad et al, 2010). Gravid H. axyridis females reduced their rates of oviposition when exposed to the feces of conspecifics, but not when exposed to the feces of heterospecifics (Propylea japonica) (Agarwala et al, 2003).…”
Section: Mate Location Mating and Ovipositionmentioning
confidence: 99%
“…When getting closer to prey, the foraging behavior becomes more intensive, with lower walking speed and more directional changes (Pettersson et al, 2005). Olfactory cues include prey pheromones (Verheggen et al, 2007, hostplant volatiles (Leroy et al, 2012a), prey waste products such as honeydew (Leroy et al, 2012b), and conspecific-associated odors (Almohamad et al, 2010;Leroy et al, 2012a). Like other insects, H. axyridis larvae deposit chemical marks as they forage.…”
Section: Prey Locationmentioning
confidence: 99%